Assessment of laparoscopic skills: Comparing the reliability of global rating and entrustability tools - Alibhai, Kameela Miriam; Fowler, Amanda; Gawad, Nada; Wood, Timothy J; Raîche, Isabelle (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
Background: Competence by design (CBD) residency programs increasingly depend on tools that provide reliable assessments, require minimal rater training, and measure progression through the CBD milestones. To assess intraoperative skills, global rating scales and entrustability ratings are commonly used but may require extensive training.  The Competency Continuum (CC) is a CBD framework that may be used as an assessment tool to assess laparoscopic skills. The study aimed to compare the CC to two other assessment tools: the Global Operative Assessment of Laparoscopic Skills (GOALS) and the Zwisch scale.Methods: Four expert surgeons rated thirty laparoscopic cholecystectomy videos. Two raters used the GOALS scale while the remaining two raters used both the Zwisch scale and CC. Each rater received scale-specific training. Descriptive statistics, inter-rater reliabilities (IRR), and Pearson’s correlations were calculated for each scale.Results: Significant positive correlations between GOALS and Zwisch (r = 0.75, p < 0.001), CC and GOALS (r = 0.79, p < 0.001), and CC and Zwisch (r = 0.90, p < 0.001) were found. The CC had an inter-rater reliability of 0.74 whereas the GOALS and Zwisch scales had inter-rater reliabilities of 0.44 and 0.43, respectively. Compared to GOALS and Zwisch scales, the CC had the highest inter-rater reliability and required minimal rater training to achieve reliable scores.Conclusion: The CC may be a reliable tool to assess intraoperative laparoscopic skills and provide trainees with formative feedback relevant to the CBD milestones. Further research should collect further validity evidence for the use of the CC as an independent assessment tool.